Association Between Nontraditional Lipid Profiles and the Risk of Type 2 Diabetes Mellitus in Chinese Adults With Hypertension: Findings From the China Hypertension Registry Study - Yu Tao; Tao Wang; Wei Zhou; Lingjuan Zhu; Chao Yu; Juxiang Li; Huihui Bao; Xiaoshu Cheng (The Journal of Clinical Hypertension)
ABSTRACT The relationship between nontraditional lipid profiles and type 2 diabetes mellitus (T2DM) remains ambiguous within the hypertension population. The objective of this study is to examine the association between nontraditional lipid profiles and T2DM in Chinese adults with hypertension. The current investigation encompassed 13 728 participants with hypertension from the China Hypertension Registry Study. Logistic regression analysis and smooth curve fitting were employed to evaluate the association between nontraditional lipid profiles and T2DM. The prevalence of T2DM was found to be 17.8%. In the fully adjusted model, atherogenic index of plasma (AIP) exhibited the highest odds ratios (ORs) for T2DM (OR: 2.71, 95% confidence interval [CI]: 2.26–3.26). Conversely, the fully adjusted ORs (95% CI) for total cholesterol (TC)/high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein cholesterol (LDL‐C)/HDL‐C, and non‐high‐density lipoprotein cholesterol (Non‐HDL‐C) were 1.33 (1.25–1.41), 1.40 (1.29–1.51), and 1.41 (1.34–1.49), respectively. Additionally, the study demonstrated that AIP had a superior ability to identify T2DM. Subgroup analyses indicated that the relationship between AIP and Non‐HDL‐C with T2DM was more significant in the lighter weight population. In addition, the association of TC/HDL‐C with LDL‐C/HDL‐C with T2DM was stronger in the lower homocysteine level population. Among the southern Chinese population with hypertension, all nontraditional lipid indices positively correlated with the risk of T2DM. Among these lipid indices, AIP exhibited superior discriminatory power in identifying T2DM compared to TC/HDL‐C, LDL‐C/HDL‐C. Trial Registration: ChiCTR1800017274